EFFECT OF CAPITAL STRUCTURE, PROFITABILITY, TAX PLANNING AND DIVIDEND POLICY ON THE VALUE OF COMPANIES LISTED ON THE IDX - Abd Rohman Taufiq; Yunita Futui Trianti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to analyze the effect of capital structure, profitability, tax planning, and dividend policy on firm value. The research method uses an indexed population of 57 consumer goods listed on the IDX in 2020 with a sample of 27 companies. The sampling technique used was purposive sampling. The results showed that the capital structure had an effect on firm value with a significant level of